2018
DOI: 10.1080/15685551.2018.1531961
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and styrene copolymerization of novel trisubstituted ethylenes: 3. Alkoxy ring-substituted isopropyl 2-cyano-3-phenyl-2-propenoates

Abstract: Novel trisubstituted ethylenes, alkoxy ring-substituted isopropyl 2-cyano-3-phenyl-2-propenoates, RPhCH = C(CN)CO2CH(CH3)2 (where R is 2-methoxy, 3-methoxy, 4-methoxy, 2-ethoxy, 3-ethoxy, 4-ethoxy, 4-propoxy, 4-butoxy, 4-hexyloxy) were prepared and copolymerized with styrene. The ethylenes were synthesized by the piperidine catalyzed Knoevenagel condensation of ring-substituted benzaldehydes and isopropyl cyanoacetate, and characterized by CHN analysis, FTIR, 1H and 13C NMR. All the ethylenes were copolymerize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The conversion of the copolymers was kept between 10 and 20% to minimize compositional drift (Table 1). Nitrogen elemental analysis showed that between 19.4 and 30.0 mol% of MEPA is present in the copolymers prepared at ST/MEPA = 3 (mol), which is indicative of relatively high reactivity of the MEPA monomers towards ST radical which is typical of alkoxy ring-substituted phenylcyanoacrylates [18][19][20][21][22]. Since MEPA monomers do not homopolymerize, the most likely structure of the copolymers would be isolated MEPA monomer units alternating with short ST sequences (Scheme 2).…”
Section: Synthesis and Characterization Of Styrene -Mepa Copolymersmentioning
confidence: 99%
See 1 more Smart Citation
“…The conversion of the copolymers was kept between 10 and 20% to minimize compositional drift (Table 1). Nitrogen elemental analysis showed that between 19.4 and 30.0 mol% of MEPA is present in the copolymers prepared at ST/MEPA = 3 (mol), which is indicative of relatively high reactivity of the MEPA monomers towards ST radical which is typical of alkoxy ring-substituted phenylcyanoacrylates [18][19][20][21][22]. Since MEPA monomers do not homopolymerize, the most likely structure of the copolymers would be isolated MEPA monomer units alternating with short ST sequences (Scheme 2).…”
Section: Synthesis and Characterization Of Styrene -Mepa Copolymersmentioning
confidence: 99%
“…Earlier we have reported synthesis and styrene copolymerization a number of alkoxy ring-substituted PCAs, such esters as methyl [18], ethyl [19], propyl [20], isopropyl [21], and butyl [22].…”
Section: Introductionmentioning
confidence: 99%
“…Yield 91%; mp 95.4°C, 1 H-NMR  8.6 (s, 1H, CH=), 7.8-6.9 (m, 3H, Ph), 5.2 (m, 1H, CH), 3.9 (s, 3H, OCH3), 1.4 (d, 6H, CH3); 13…”
Section: Isopropyl 2-cyano-3-(2-bromo-5-methoxyphenyl)-2-propenoatementioning
confidence: 99%
“…Copolymerization of TSE having double bonds substituted with halo, cyano, and carbonyl groups and electron-rich monosubstituted ethylenes such as styrene, Nvinylcarbazole, and vinyl acetate (7)(8)(9) show a tendency toward the formation of alternating copolymers. Thus, some ring-substituted MCPP and ECPP monomers were copolymerized with styrene (10, 11) and vinyl acetate (12,13). Recently we have reported synthesis and styrene copolymerization of a number of novel isopropyl 2-cyano-3-phenyl-2-propenoates (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, copolymerization of electrophylic TSE monomers having double bonds substituted with halo, cyano, and carbonyl groups and electron-rich monosubstituted ethylenes such as styrene, N-vinylcarbazole, and vinyl acetate [13][14][15] show a tendency toward the formation of alternating copolymers -thus suggesting a way of functionalization of commercial polymers via introduction of isolated monomer units in copolymers. Earlier we have reported synthesis and styrene copolymerization a number of alkoxy ring-substituted PCAs, such esters as methyl [16], ethyl [17], propyl [18], isopropyl [19], and butyl [20].…”
Section: Introductionmentioning
confidence: 99%